Efficiency and Profitability of Tanzanian saving and Credit Cooperatives: Who is a Star? - Marwa, Nyankomo (Journal of Economics and Behavioral Studies, 2014)
The objective of this paper is to evaluate and benchmark the performance of Tanzanian Saving and Credit Cooperatives (SACCOs). Measuring the performance of these organizations is useful in helping them to monitor and control their performance and business processes and improve productivity and profitability. The study used secondary data from audited financial statements from 103 SACCOs. Technical efficiency was estimated using the data envelopment analysis approach and profitability was measured using return on assets. Then an efficiency-profitability matrix was employed to distinguish best performers from struggling SACCOs. This particular approach has been selected to account for multiple dimensions of performance measures. Using the top 25% as a cut-off for profitability and efficiency we found that only 12% of the firms were diagnosed as best performers (stars). The majority of the firms (61%) were classified under the low efficiency low profitability category. Fourteen SACCOs were highly profitable but had low efficiency scores, which demonstrate a potential for performance improvement by increasing their efficiency. Another group of 14 SACCOs were classified as potential candidates for divestiture because they had high efficiency scores but low profitability. Conclusively the performance of the industry in Tanzania needs a well-thought turnaround strategy to make it commercially viable. For the majority of the SACCO both profit-increasing and efficiencyincreasing strategies are required.